An experimental study on characterizing damage and fracture of a rock-like material based on three-dimensional magnetic field imaging. Issue 5 (20th October 2020) - Yue, Wenping; Yang, Mingyang
Abstract : Purpose: The results showed that the use of a magnetic marker could relatively accurately reflect the fracture pattern inside the rock-like material (RLM). Design/methodology/approach: This study investigated the internal structure and fracture pattern of a fractured RLM. Magnetized iron oxide powder, which was used as a magnetic marker, was mixed with water and glue to form a magnetic slurry, which was subsequently injected into a fractured RLM. After the magnetic slurry completely filled the cracks inside the RLM and became cemented, the distribution and magnitude of the magnetic field inside the RLM were determined using a three-dimensional (3D) magnetic field imaging system. Findings: A model for determining the magnetic field strength was developed using MATLAB. Originality/value: This model of 3D magnetic will further be used as a finite element tool to simulate and image cracks inside the rock.